Studi Perbandingan Regulasi Tindak Pidana Memperdagangkan Produk Yang Tidak Sesuai Dengan Informasi Komposisi Ditinjau Dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen dan Undang-Undang No 7 Tahun 2014 tentang Perdagangan - Jasmine Kirana, Najwa; Toni, Toni; Agustian, Rio Armanda (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Products that do not match the composition information, is a product that is in the product label that is not in accordance with the content of the content that should be, for example the data manipulation and / or information. The purpose of this study to analyze and know the right criminal law and accurating the right criminal sanctions in the case of trading products that do not match the composition information. The research method used is normative juridical research, while the approach used is the approach of legislation. The results of this study show that each rule of regulation of criminal acts has their weaknesses and excess, so that the ratio of law between the two. So the basis of legal certainty of the principle of legality, the right criminal law in the object of this research is the trade law in Article 108. And in accordance with the right criminal sanction in this case by using the legal comparison between consumer protection laws with trade laws. So the right criminal sanction to be given in deeds of trading products that do not match the composition information of trade law in Article 108. The conclusion is from the object of this research the proper criminal law with the two rules of regulation of the criminal actions reinforced by the Concursus idealist theory in the Criminal Code of Article 63 paragraph (2) of the trade law, and so do the criminal law in the object of the research.